Preparation and In vitro Characterization of Aceclofenac Nanosuspension (ACNS) for Enhancement of Percutaneous Absorption using Hydrogel Dosage Form - Aseel Kadhem Thamer; Ahmed Najem Abood (College of Pharmacy University of Baghdad, 2021)
Aceclofenac (AC) is an orally active phenyl acetic acid derivative, non-steroidal anti-inflammatory drug with exceptional anti-inflammatory, analgesic and antipyretic properties. It has low aqueous solubility, leading to slow dissolution, low permeability and inadequate bioavailability. The aim of the current study was to prepare and characterize AC-NS-based gel to enhance the dissolution rate and then percutaneous permeability. NS.s were prepared using solvent/antisovent precipitation method at different drug to polymer ratios (1:1, 1:2, and 1:3) using different polymers such as poly vinyl pyrrolidone (PVP-K25), hydroxy propyl methyl cellulose (HPMC-E5) and poloxamer® (388) as stabilizers alone and in combinations of two polymers (1:2 and 1:4 Drug: polymer ratio). Fifteen formulas of AC-NS.s were prepared and characterized for production yield, loading efficiency, particle size, polydispersity index and physical stability. The best formulas of NS were then lyophilized to be characterized by FTIR, DSC, P-XRD and SEM. After that, the best prepared formula of AC-NS regarding the involved characterization methods was incorporated in gel dosage forms using carbopol®940. From this study, we conclude that the dissolution rate and permeability of AC were improved when the particle size was reduced to Nano-scale as compared with pure drug.